Kinerja Perbankan dan Implikasinya terhadap Dividend Payout Ratio pada Perbankan Indonesia - Puspita Rama Nopiana; Wellia Novita (Jurnal Riset Ekonomi dan Akuntansi, 2026)
Dividend policy is one of the key indicators used by investors to assess the stability and financial performance of banking companies. This study aims to analyze the effect of financial performance on the Dividend Payout Ratio in conventional banks in Indonesia during the 2021–2024 period. Financial performance is proxied by liquidity, Leverage, and profitability. This research employs a quantitative approach with an associative research design. The population consists of 43 conventional commercial banks listed on the Indonesia Stock Exchange up to 2024. The sampling technique uses purposive sampling, resulting in 24 conventional banks with a total of 96 panel data observations. The data used are secondary data obtained from the companies’ annual financial statements and analyzed using multiple linear regression. The results show that liquidity, proxied by Loan to Deposit Ratio (LDR), has a positive and significant effect on the Dividend Payout Ratio; Leverage, proxied by Debt to Asset Ratio (DAR), has a negative and significant effect on the Dividend Payout Ratio; and profitability, proxied by Return on Assets (ROA), has a positive and significant effect on the Dividend Payout Ratio. Furthermore, liquidity, Leverage, and profitability simultaneously have a significant effect on the Dividend Payout Ratio in conventional banks in Indonesia. This study indicates that the company’s financial performance is a key factor in determining dividend policy in the banking sector.